Design and application of blockchain pattern for credit information industry - Shuohang GUO; Ziqi SONG (网络与信息安全学报)
Based on the current status of Chinese credit information system,expounding the problems arising from the traditional credit information system structure,a credit system structure based on blockchain technology and two data transaction pattern and the technical framework of the credit data trading platform was proposed,It has the characteristics of decentralization,safe and credible,collective maintenance,and untampering.And the process of data transaction were expounded.To explore the advantage of application of blockchain in the credit and information industry:promote credit data sharing,improve the quality of supervision of the credit and information industry,ensure the privacy of the information subject,effectively improve the dimension of credit information.